Organizational barriers in HPV vaccination uptake: A cross-sectional study among health sciences students - Giuseppina Palena; Irene Stilo; Michele Sorrentino; Claudio Fiorilla; Raffaele Palladino (PLoS ONE, 2025)
Background Human papillomavirus (HPV) is a leading cause of cervical, anal, and oropharyngeal cancers. Despite the proven effectiveness of HPV vaccination, uptake remains low, particularly among males and specific demographic groups. In Italy, national HPV vaccination coverage stagnated at 38.8% in 2022, with significant regional disparities. While previous studies have explored individual and cultural barriers, organizational challenges within academic institutions remain underexamined. The aim of this cross-sectional study was assessing the uptake of HPV vaccination among Health Sciences students at the University of Naples Federico II. Methods An anonymous online survey collected data on demographics, vaccination status, and institutional barriers. Logistic regression models were used to identify predictors of vaccination, adjusting for demographic factors, institutional communication, and knowledge-attitude scores. Results Among 354 participants, 55.1% reported receiving at least one HPV vaccine dose. Female students had significantly higher vaccination rates (aOR: 7.95; 95% CI: 4.24–14.90), while older age was associated with lower uptake (aOR: 0.81; 95% CI: 0.73–0.91). Institutional vaccination invitations increased the likelihood of vaccination nearly threefold (aOR: 2.81; 95% CI: 1.48–5.33). Attitudes toward vaccination strongly predicted uptake, whereas knowledge scores showed no significant association. Conclusions These findings highlight the need for structured institutional interventions, including targeted education, proactive vaccination invitations, and improved access to on-campus vaccination services. Strengthening university-led initiatives could significantly enhance HPV vaccine uptake among future healthcare professionals, contributing to broader public health efforts in HPV-related cancer prevention.